Pancreas Cystic Lymphangioma Diagnosed with EUS-FNA - Coe, Adam W; Evans, John; Conway, Jason (JOP. Journal of the Pancreas, 2012)
Context Endoscopic ultrasound has proved to be an invaluable tool when obtaining high quality images of the pancreas. Furthermore, fine-needle aspiration of suspected lesions can be carried out simultaneously thus providing tissue samples for cytologic diagnosis. We present two cases of a rare pancreatic lesion that were diagnosed by endoscopic ultrasound with fine-needle aspiration. Case #1 A 60-year-old asymptomatic gentleman was found to have an incidental pancreatic lesion on abdominal computed tomography scan during a cardiac workup. Patient had no personal or family medical history that would predispose him to pancreatic lesions. Endoscopic ultrasound was performed and patient was diagnosed with pancreatic cystic lymphangioma. Case #2 A 40-year-old asymptomatic gentleman with history of heavy alcohol use was found to have an incidental pancreatic lesion on computed tomography scan during a work up of chest pain. Computed tomography guided fine-needle aspiration was negative for malignancy but no other studies were performed on the fluid sample at that time. Patient was then referred to our institution after repeat computed tomography scan showed a stable lesion. Endoscopic ultrasound did not show evidence of pancreatitis and fine-needle aspiration was consistent with pancreatic cystic lymphangioma. Discussion The universally available and escalating use of computed tomography scans has led to an increased detection of incidental cystic pancreatic lesions. Pancreatic cystic lymphangiomas are a rare lesion and account for less than one percent of all pancreatic cystic lesions. These lesions are easily and accurately diagnosed by the use of endoscopic ultrasound guided fine-needle aspiration.